The Influence of Personality, Behavior, and Environment on Self-Regulated Learning of Students - Hrp, Cyndi Aulia Pangolangan; Fadhli, Muhammad (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
Analyzing the influence of personality, behavior, and environment on students' self-regulated learning at Madrasah Aliyah Negeri 1 Medan is the objective of this study. The approach used in this study is quantitative with a survey method. The determination of the number of samples is based on the Krejcie and Morgan table, which indicates that the population used is 601 students, so that 234 respondents will be obtained as research samples. Data were collected using a questionnaire instrument, then analyzed through statistical tests to determine the relationship and influence between variables. Based on the results of the research that has been conducted, it was found that the student's personality variable significantly has a positive impact on their ability to carry out self-regulated learning with a path coefficient value of 0.474, p-value 0.000, and t-statistic 5.024. The behavioral variable also has a positive and significant effect on self-regulated learning with a path coefficient value of 0.375, p-value 0.000, and t-statistic 5.763. Meanwhile, environmental variables have a positive but insignificant influence on self-regulated learning, as reflected by the path coefficient of 0.040, p-value of 0.618, and t-statistic of 0.499. The research findings indicate that personality is the variable with the highest coefficient value in influencing students' self-regulated learning. Thus, internal factors such as personality and behavior have a stronger contribution than environmental factors in improving students' ability to regulate and control their learning process independently.